Single Cross Hybrid: A Potential Technology for Boosting Maize Production - Dass, S.; Karjagi, C. G.; Kumar, Bhupender; Jat, S. L.; Parihar, C. M.; Kumar, Ramesh; Kamboj, M. C. (Indian Farming, 2015)
The growing demand for single cross hybrid seed is an opportunity for seed industry growth. India has already developed strong network of seed production agencies like NSC, SFCI, NGOs, and Private Seed Companies supported by several crop specific research institutions established under ICAR, SAUs. The favourable government policies also in place therefore the task of availability of sufficient quantity of quality seed to farmers does not seem difficult to achieve. The hybrid seed production is largely ( 90%) concentrated in Andhra Pradesh and and there is 100% area under hybrid is the state that is why AP has highest productivity in the country. There is need to replicate the model of Andhra Pradesh across different states of the country. Therefore, several alternative seed production sites viz., E. India: WB - Midnapur, Krishna Nagar, Bihar - Muzaffurpur, Begusarai, Somastipur etc (rabi); W. India: Gujarat-Panch mahal, Dahud, Rajasthan-Banswara, Dungarpur (rabi); C. India: MP - Chindwada, Indore, Ratlam, Jabalpur, Hinday, Chhattisgarh – Chhattisgarh, Raipur (rabi); S. India: MH - Aurangabad, Ahmednagar, KA - Bellary, Raichur, Shimoga (rabi); N. India: E.UP in rabi, UK in Spring, J&K – Jammu, Himachal – Unna were also identified to achieve the availability of hybrid seed at local places.